Changes in musculoskeletal disease activity and patient-reported outcomes in patients with psoriatic arthritis treated with ixekizumab: results from a real-world US cohort - Tillett, William; Birt, Julie; Cavanaugh, Cristi; Jung, Yoojin; Vadhariya, Aisha; Ross, Sarah; Paulus, Jessica; Lubrano, Ennio (Frontiers in Medicine, 2023)
Introduction Ixekizumab has demonstrated efficacy in pivotal trials in patients with psoriatic arthritis (PsA), both those naïve to prior biologic therapy and those with prior inadequate response or intolerance to biologics; however, minimal information is currently available on the effectiveness of ixekizumab in routine clinical practice. The objective of this study was to investigate the clinical effectiveness of ixekizumab for the treatment of PsA over 6- and 12-month follow-up periods in a real-world setting. Methods This retrospective cohort study included patients who initiated treatment with ixekizumab from the OM1 PremiOMTM PsA dataset, a dataset of over 50,000 patients with claims and electronic medical record (EMR) data. Changes in musculoskeletal outcomes, such as tender and swollen joint count and patient-reported pain, as well as physician and patient global assessment, as measured using the Clinical Disease Activity Index (CDAI), and Routine Assessment of Patient Index Data 3 (RAPID3) were summarized at 6 and 12 months. The RAPID3, CDAI score, and their individual components were assessed in multivariable regressions adjusting for age, sex, and baseline value. The results were stratified by biologic disease-modifying antirheumatic drug (bDMARD) status (naïve vs. experienced) and monotherapy status (monotherapy vs. combination therapy with conventional synthetic DMARDs). Changes in a 3-item composite score derived from a physician global assessment, patient global assessment, and patient-reported pain score were summarized. Results Among the 1,812 patients identified receiving ixekizumab, 84% had prior bDMARD treatment and 82% were monotherapy users. All outcomes improved at 6 and 12 months. For RAPID3, the mean (SD) change at 6 and 12 months was −1.2 (5.5) and −1.2 (5.9), respectively. Patients overall, bDMARD experienced, and monotherapy patients achieved statistically significant mean change in CDAI and all components from baseline to 6 and 12 months in adjusted analyses. Patients experienced an improvement in the 3-item composite score at both time points. Conclusion Treatment with ixekizumab was associated with improvements in musculoskeletal disease activity and PROs as assessed by several outcome measures. Future research should assess ixekizumab's clinical effectiveness in the real world across all PsA domains using PsA-specific endpoints.